Physical Activity is not Necessary: The Notion of Sport as Unproductive Officialised Competitive Game. Issue 1 (2nd January 2022) - Lebed, Felix
ABSTRACT: Every cultural phenomenon is multifaceted and only with great difficulty can it fit into the framework of one general concept. The term 'sport' is such a broad concept, because the great wealth of meanings it has absorbed makes definition quite difficult. A list of only its main connections include: human play and pastime accompanied by physical activity, fair-play competition, and moral norms of honest behaviour in resolving conflicts. Attempts to suggest a definition of sport encounter several logical difficulties, the main one of which seems to me to be the binding of this category to physical activity as a basic and even exclusive property. In trying to comprehend sport, I attempt in this article to transfer the centre of gravity in reasoning from physical activity (a concept that I try to consider more accurately) to three other properties that are necessary and which taken together are sufficient for understanding sport as a category. These are: unproductiveness (as opposed to playing performances in arts), attachment to competitive game as a special form of human play, and the public and widely accepted official status and functioning of such game. Based on these considerations, I propose a new definition of sport.